Strategi Pemerintah Desa Dalam Proses Pengendalian Schistosomiasis Di Desa Watumaeta Kecamatan Lore Utara Kabupaten Poso - sefia dewi, jesica; Djaelangkara, Rizali; Mayusa, Askar (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
The aim of this research is to find out the Village Government's Strategy in the Process of Controlling Schistosomiasis in Watumaeta Village, North Lore District, Poso Regency.